A waste of time and effort? Benefit and factors of success of cross-border cooperation in urban and regional development in the German-Polish-Czech triangle - Knippschild, Robert (Raumforschung und Raumordnung | Spatial Research and Planning, 2009)
Stakeholders in public authorities are often sceptical towards cross-border cooperation projects in spatial development. The reason for this is that the benefit too often remains unclear, even after the closure of such processes that are in many cases funded by EU Programmes. A reasonable expenditure of European subsidies for cross-border cooperation becomes a challenge. But it is up to the stakeholders themselves to benefit from the achieved results of cooperation. This requires a longterm perspective, joint and realistic objectives and expectations as well as skills for dealing with existing constraints of cooperation.